Migrant Workers Who Are Citizens of The Republic of Indonesia in The Fisheries Sector Working on Foreign-Flagged Vessels from a Legal and Economic Perspective - Ade Hari Siswanto; Nina Nurhasanah; Sri Redjeki Slamet; Amir Bakhtiar; Steven Alexander Morgan (International Journal of Science and Environment (IJSE), 2026)
The exploitation and human trafficking practices against Indonesian migrant workers employed on foreign-flagged fishing vessels demonstrate the weakness of cross-jurisdictional legal protection. This study aims to analyze the regulatory framework governing legal protection for migrant workers in the fisheries sector; to examine the legal strategies and policies that may be developed to strengthen such protection. The research employs a normative juridical method, incorporating statutory, conceptual, and case approaches, and uses qualitative descriptive analysis of primary, secondary, and tertiary legal materials. The findings indicate that Law No. 18 of 2017 and Government Regulation No. 22 of 2022 provide a strong legal basis in Indonesia; however, inter-agency coordination gaps and limited cross-border supervision hinder their effective implementation. To reinforce both legal and economic protection, institutional synergy, consistent supervision, and the ratification of the ILO Convention No. 188 of 2007 and the Cape Town Agreement of 2012 as supporting international legal instruments are required. This study contributes to the strengthening of institutional and cross-jurisdictional policy synergy to ensure the protection of Indonesian migrant workers in the fisheries sector through an integrated legal and economic approach.